L-Asparaginase and the effect of age on coagulation and fibrinolysis in childhood acute lymphoblastic leukemia - Appel, Inge M.; Hop, Wim C. J.; van Kessel-Bakvis, Carla; Stigter, Rolinda; Pieters, Rob (Thrombosis and Haemostasis, 2008)
Alterations in haemostasis are frequently observed in children with acute lymphoblastic leukemia (ALL). It was the objective of this study to analyse age-related disturbances in coagulation and fibrinolysis parameters during the induction phase of the anti-leukemic treatment. Sixty-four children were classified by age into three groups (1–5, 6–10, 11–16 years), and studied during induction treatment of ALL including four weeks of dexamethasone, followed by two weeks tapering of dexamethasone during which 6,000 IU/m2 native L-Asparaginase (total 4 doses) was administered intravenously twice weekly. Blood samples were collected immediately before each L-Asparaginase infusion to analyze procoagulant (fibrinogen, factor [F] II, FV, FVII, F IX, F X) and anticoagulant factors (antithrombin [AT], protein C, protein S), parameters of thrombin generation (F1+2, TAT) and fibrinolysis (α2-antiplasmin, plasminogen, PA P , D-dimer). Children were in a hypercoagulable state after four weeks of dexamethasone due to upregulation of coagulation parameters. Upregulation was highest in the two youngest age groups. During L-Asparaginase treatment the 11– to 16-year- olds showed lower values in procoagulant and, even more, in anticoagulant factor levels compared to the younger children. Activation markers of thrombin generation and fibrinolysis did not change over time during the study period. Decreased synthesis of α2-antiplasmin and plasminogen during L-Asparaginase treatment resulted in less potential of clot lysis by plasmin in children older than 11 years of age. In conclusion, a more severe decline of anticoagulant and fibrinolytic parameters in children between 11 and 16 years of age underline that these children are at higher risk of thrombosis during ALL induction treatment.
Keywords: ALL; developmental haemostasis; L-Asparaginase